1993
DOI: 10.1161/01.cir.88.3.837
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-arm index as a marker of atherosclerosis in the Cardiovascular Health Study. Cardiovascular Heart Study (CHS) Collaborative Research Group.

Abstract: There was an inverse dose-response relation of the AAI with CVD risk factors and subclinical and clinical CVD among older adults. The lower the AAI, the greater the increase in CVD risk; however, even those with modest, asymptomatic reductions in the AAI (0.8 to 1.0) appear to be at increased risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
733
7
25

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,025 publications
(804 citation statements)
references
References 41 publications
39
733
7
25
Order By: Relevance
“…AAI was defined as the lowest ratio of SBP of either the right ankle to the right upper-arm or the left ankle to the right upper-arm. According to previous reports of abnormal AAI associated with preclinical cardiovascular disease, 21 AAI p0.9 in either leg was used to define LEAD.…”
Section: Definition Of Leadmentioning
confidence: 99%
“…AAI was defined as the lowest ratio of SBP of either the right ankle to the right upper-arm or the left ankle to the right upper-arm. According to previous reports of abnormal AAI associated with preclinical cardiovascular disease, 21 AAI p0.9 in either leg was used to define LEAD.…”
Section: Definition Of Leadmentioning
confidence: 99%
“…It was shown that an ABI of less than 0.90 was 95% sensitive and 99% specific for diagnosing angiographically defined PAD [16]. Individuals with an ABI greater than 1.50 were excluded from this study as it indicated poorly compressible leg arteries [17,18].…”
Section: Assessment Of Peripheral Atherosclerosismentioning
confidence: 99%
“…A commonly used non-invasive test for peripheral arterial disease is the measurement of systolic blood 12 thus raising several methodological problems, [11][12][13][14][15] which involved: differences in geometry between the two ankle vessels; difference in pressures between the right and left legs; and the decrease in brachial arterial pressure over time which would result in the higher pressure occurring in the leg first measured. [11][12][13][14][15]25,26 For all these reasons, in the present study three measurements were performed on each artery of each limb after 15 min rest and the mean value was taken as the ankle systolic blood pressure.…”
Section: Considerations On the Abi Ratiomentioning
confidence: 99%
“…[11][12][13][14][15] Below the value of 0.94, this ratio is considered to be a clear-cut indicator for arterial occlusion. More recently, the ABI ratio has been recognised to be per se an independent predictor of cardiac risk in subjects with systolic hypertension in the elderly.…”
Section: Introductionmentioning
confidence: 99%